First reported case of septo-optic dysplasia in Lara state, Venezuela (Revista Venezolana de Salud Pública, 2018)
The Septo-Optic Dysplasia is a congenital hypoplasia of the optic nerves, structural alterations in the midline of the brain, primarily the absence of septum pellucidum and pituitary hypothalamic dysfunction, which is unstable. This paper describes the findings of a patient infant with septo-optic dysplasia, who is referred to the Genetics Medical Health Sciences of the University "Lisandro Alvarado". Findings are discussed, literature is reviewed and compared the features of this patient with the literature indicated. A diagnosis of Septo-Optic Dysplasia using this physical findings and neuro imaging.